Atomic optical spatial mode extractor for vector beams based on polarization-dependent absorption - Chang, Hong; Yang, Xin; Wang, Jinwen; Ma, Yan; Yang, Xinqi; Cao, Mingtao; Zhang, Xiaofei; Gao, Hong; Dong, Ruifang; Zhang, Shougang (Chinese physics B, 2023)
Vector beams with spiral phase and spatially varying polarization profiles have many applications from optical micromanipulation to materials processing. Here, we propose and demonstrate an atomic spatial mode extracting scheme for the vector beam based on polarization-dependent absorption in the atom vapor. By employing the linear polarization pump beam which induces polarization sensitive absorption in the atomic ensemble, a counter-propagated weak probe vector beam is extracted by spatial absorption, and extracted part still maintains the original polarization and the vortex phase. The topological charges of the extracted mode are verified by interfering with the Gaussian beam, and it can be found that the orbital angular momentum is conserved in the extracting process. Our work will have potential applications in non-destructive spatial mode identification, and is also useful for studying higher-dimensional quantum information based on atomic ensembles.